Genome‐wide analysis of chitinase genes and their varied functions in larval moult, pupation and eclosion in the rice striped stem borer, Chilo suppressalis. Issue 4 (15th April 2016) - Su, C.; Tu, G.; Huang, S.; Yang, Q.; Shahzad, M. F.; Li, F.
Abstract: Some insect chitinases are required to degrade chitin and ensure successful metamorphosis. Although chitinase genes have been well characterized in several model insects, no reports exist for the rice striped stem borer, Chilo suppressalis, a highly destructive pest that causes huge yield losses in rice production. Here, we conducted a genome‐level analysis of chitinase genes in C. suppressalis . After amplification of full‐length transcripts with rapid amplification of cDNA ends, we identified 12 chitinase genes in C. suppressalis . All these genes had the conserved domains and motifs of glycoside hydrolase family 18 and grouped phylogenetically into five subgroups. C. suppressalis chitinase 1 ( CsCht1 ) was highly expressed in late pupae, whereas CsCht3 was abundant in early pupae. Both CsCht2 and CsCht4 were highly expressed in larvae. CsCht2 was abundant specifically in the third‐instar larvae and CsCht4 showed periodic high expression in 2‐ to 5‐day‐old larvae in each instar. Tissue specific expression analysis indicated that CsCht1 and CsCht3 were highly expressed in epidermis whereas CsCht2 and CsCht4 were specifically abundant in the midgut. Knockdown of CsCht1 resulted in adults with curled wings, indicating that CsCht1 might have an important role in wing expansion. Silencing of CsCht2 or CsCht4 arrested moulting, suggesting essential roles in larval development. When the expression of CsCht3 was interfered, defects in pupation occurred. Overall, we provide here the first catalogue of chitinase genes in the rice striped stem borer and have elucidated the functions of four chitinases in metamorphosis.